A review on the synthesis of MXenes and their lubrication performance and mechanisms. (January 2023) - Lu, Xinyu; Gu, Xiaoli; Shi, Yijun
Abstract: MXenes (MXs), as an emerging 2D family of transition metal carbides and nitrides, have been considered as new candidates for solid lubrication/lubricant additives due to their mono-layered graphene-like structure with similar mechanical properties, abundant surface terminations (i.e., -O, -OH, -F), relatively low shear strength and inherent self-lubrication ability. In this review, we introduced MXs' synthesis and their lubrication performance and mechanisms. Typically, pure MXs and MXs-based composites like MXs/polymers, MXs/graphene (MoS2 ) or MXs/metals (metal oxide) were used as reinforcement materials to form protective coatings with excellent mechanical properties and solid lubrication performance. As liquid lubricant additives, MXs can be used as water-/oil-based lubricant additives, and exhibit improved friction and wear. At the same time, chemically functionalized MXs with better dispersibility and compatibility were introduced as the improved oil-based lubricant additives. Some parameters (such as MXs' structural effects and working conditions) affecting MXs' lubrication performance, and the lubrication mechanisms (such as the formation of tribofilm, the hydrophilicity-/interlayer-dependent lubrication mechanism and adsorption effect) were all discussed. Finally, some future perspectives for MXs' lubrication were proposed at the end of this review.